Metodologia archeologii/prahistorii profesora dr. hab. Jana Żaka (1923–1990) po 30 latach. Między modernistycznymi dążeniami a postmodernistyczną rzeczywistością - Minta-Tworzowska, Danuta (Folia Praehistorica Posnaniensia, 2021)
January 4, 2020 was the 30th anniversary of the death of Professor Jan Żak, who died prematurely at the age of 67. His work and scientific activities were known and appreciated in various countries and during difficult times when he was professionally involved in archeology. The biography of Professor Jan Żak resulted largely from the spirit of the times in which he lived, but also from his open, curious personality. He touched the warfare, and his professional life took place in the realities of the People's Republic of Poland; he also witnessed its dramatic end. The aim of this article is not only to recall the methodological and theoretical foundations of J. Żak's scientific work, but also to try to answer the question about the contemporary methodology of archeology, practiced by the Professor's students and subsequent generations.